Additional Intraocular Surgery after Pediatric Cataract Surgery - Mario R Papilaya; Feti K Memed; Andrew M Knoch (Majalah Oftalmologi Indonesia, 2015)
Background: Advances in pediatric cataract surgery have led to decrease in complication rates, nevertheless additional intraocular surgery (AIS) often still required after pediatric cataract surgery to maximize the outcome. This study aims to review the clinical characteristic of children who underwent AIS in National Eye Center Cicendo Eye Hospital Method: Patient medical records were reviewed retrospectively. Patients then divided into two groups depending on type of AIS. Group A were the children who underwent secondary intraocular lens (IOL) implantation and group B were the children who underwent surgery to repair visual axis opacity. Result: There were 24 eyes in group A and 16 eyes in group B. Mean age at cataract surgery in group A and B were 14.7 and 41.14 months, mean age at AIS in group A and B were 73.8 and 100.3 months, mean time length were 59.6 and 57.6 months in group A and B. Patient in group A had better visual outcome compared to group B. 68.75 % eyes in group B were pseudophakic. Conclusion: Patient in group A had a younger age compared to group B, mean length time between surgery were similar in both group. Patient in group A had better BCVA compared to group B with most of the patients who need VAO surgery were pseudophakic. Keywords: Additional intraocualar surgery, pediatric cataract, secondary IOL